The book of common prayer a very short introduction - Cummings, Brian ca. 20./21. Jh (Very short introductions, 2018)
'The Book of Common Prayer' is one of the most influential books in history. Brian Cummings tell its fascinating story, charting its spread from England to reach the world, and showing how the book has divided conformity from non-conformity, in social terms as well as religious, from birth to marriage to death